1993
DOI: 10.1109/10.237690
|View full text |Cite
|
Sign up to set email alerts
|

A test for teratological effects of power frequency magnetic fields on chick embryos

Abstract: An analysis of 13 studies of the teratological effects of pulsed magnetic fields on chick embryos from ten independent laboratories permits no clear conclusions. Comparatively little has been done to follow up on the reports by Juutilainen and coworkers on the effects of extremely low-frequency, sinusoidal magnetic fields on the malformation rate in chick embryos. Our attempt to follow up on their results using similar but not identical exposures of 10 microT, 50 Hz magnetic fields produced negative results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Veterany and Hluchy (2001) and Toman et al (2002) reported that hatchability of hen eggs subjected to a magnetic field during storage prior to setting was increased, but hatchability of eggs treated with a magnetic field during incubation was decreased. Cox et al (1993) did not find any developmental anomalies after treating hen eggs with a magnetic field of 50 Hz and 10 µT in the first 52 hours of incubation. Coulton and Barker (1991) stated that the effects attributed to the action of magnetic field might be a derivative of disturbances in hatching parameters.…”
Section: Resultsmentioning
confidence: 68%
“…Veterany and Hluchy (2001) and Toman et al (2002) reported that hatchability of hen eggs subjected to a magnetic field during storage prior to setting was increased, but hatchability of eggs treated with a magnetic field during incubation was decreased. Cox et al (1993) did not find any developmental anomalies after treating hen eggs with a magnetic field of 50 Hz and 10 µT in the first 52 hours of incubation. Coulton and Barker (1991) stated that the effects attributed to the action of magnetic field might be a derivative of disturbances in hatching parameters.…”
Section: Resultsmentioning
confidence: 68%
“…Cox et al [1993] attempted to partly replicate the findings of Juutilainen et al No difference from control embryos was observed in 200 embryos exposed to a 10 mT, 50 Hz magnetic field. Farrell et al [1997] conducted an extensive series of experiments on the effects of pulsed and sinusoidal magnetic fields on chick embryo development, involving a total of more than 2500 embryos.…”
Section: Magnetic Fields: Non-mammalian Speciesmentioning
confidence: 83%
“…They were surrounded by fragments of rough endoplasmic reticulum and lots of free ribosomes. It was reported that mitochondria is the source of free radicals produced in response to electromagnetic wave exposure in human sperms [22]. It further reported potential causative mechanism of electron leakage from the mitochondrial electron transport chain which causes oxidative DNA damage.…”
Section: Histology and Electron Microscopymentioning
confidence: 97%
“…Production of heat shock proteins is stimulated to repair this damage. This also increases reactive oxygen species production and apoptosis [17,22,23]. DNA damage if not repaired would most likely result in cell death [23].…”
Section: Gross Malformationsmentioning
confidence: 99%
See 1 more Smart Citation